In Vitro Phototoxicity and Antimicrobial Activity of Volatile Oil Obtained from Some Aromatic Plants. Issue 3 (4th May 2017) - Erdogan Eliuz, Elif Ayse; Ayas, Deniz; Goksen, Gulden
Abstract: Aromatic plants comprise many biologically active compounds such as mainly anti-microbial, anti-oxidant, anti-parasitic, anti-fungal and anti-inflammatory characteristics. The demand for these plants and their derivatives has became popular since they are natural and generally recognized as safe products. Thus, chemical composition of volatile oils, obtained from Myrtus communis (Myrtle), Citrus sinensis (Lemon), Cinnamomum zeylanicum (Cinnamon), Laurus nobilis (Laurel), and Lavandula stoechas (Lavender) were analysed. It was reported that the main components of M. communis were 1, 8 cineole (29.68 %), linalool (15.03 %), α-pinene (12.41 %) while volatile components of C. sinensis were found to be limonene (57.78 %), β-pinene (10.38 %). C. zeylanicum contained cinnamaldehyde (34.31 %), propylene glycol acetal (26.82 %), cinnamal (16.54 %). The components of L. nobilis were 1, 8 cineole (29.75 %), camphor (9.85 %). In addition, L. stoechas contained camphor (36.69 %), α-thujene (21.37 %), 1, 8 cineole (11.96 %). In this study, The minimum inhibitory concentration (MIC) and Minimal Bactericidal Concentration (MBC) were determined by using microbroth dilution technique. In addiition, in vitro, phototoxicity of volatile oil were researched against Escherichia coli (ATCC 25293), Klebsiella pneumoniae (10031), Salmonella thyphimurium, Bacillus subtilis (ATCC 6633), Staphylococcus aureus (ATCC 25925), Enterococcus feacalis (ATCC 29212) by using disc diffusion method. We showed that microoganisms were inhibited by volatile oil photoinduced using a standard LED light. Volatile oils of M. communis, L. nobilis and L. stoechas have significantly phototoxic activity against bacteria ( P < 0.05), while minor phototoxicity was induced by C. zeylanicum and C. sinensis Consequently, volatile oils of those plant could be utilized as photosensitizer agent in antimicrobial photodynamic therapy.